Aristobia horridula Hope (Coleoptera: Lamidae) a new pest of Shisham (Dalbergia sissoo Roxb.) in West Bengal - Mishra, S. C.; Veer, Vijay; Chandra, Avinash (Indian Forester, 1985)
A new insect pest, Aristobia horridula Hope, of Dalbergia sissoo is recorded from West Bengal. About 80 to 90 per cent of trees of Dalbergia sissoo plantation was affected at the time of observation.